Assessment of activity indexes on the splitting tensile strengthening of geopolymer concrete incorporating supplementary cementitious materials. (September 2020) - Oyebisi, Solomon; Ede, Anthony; Olutoge, Festus; Ngene, Ben
Graphical abstract: Highlights: GGBFS exhibits both pozzolanic and hydraulic activities. CCA exhibits pozzolanic activity. The hydraulic activity of GGBFS-CCA blends increases as CaO, MgO, and Al2 O3 increase. Pozzolanic activity of GGBFS-CCA blends increases as SiO2 and Al2 O3 increase. AIs significantly correlate with the splitting tensile strength of GGBFS-CCA GPC. Abstract: The negative effects of Portland cement production and utilization on the environment, globally demand a need for environmentally-friendly materials for the production of sustainable material in the construction sector. Therefore, this study harnessed supplementary cementitious materials (SCMs), ground granulated blast furnace slag (GGBFS) and corncob ash (CCA), for the production of geopolymer concrete (GPC). Corncob was dehydroxylated under a closed condition at 600 °C for 3 h and partially used as a substitution for GGBFS at 0 %, 20 %, 40 %, 60 %, 80 %, and 100 %. Sodium of both silicate gel and hydroxide pellets were mixed and used as activators in 12 M, 14 M, and 16 M concentrations. The oxide compositions of each and blended binder were analyzed. Consequently, the chemical moduli of each and blended binder were determined and evaluated, hence leading to the quantification of activity indexes (AIs). Moreover, the AIs and concrete mix design properties (CMDPs) were applied to predict the splitting tensile strength. Compared with the experimental results, the predictive splitting tensile strengths based on the AIs and the CMDPs yielded a high precision with 95 % R 2 . Therefore, the model equations developed by this study can be used in the concrete mix design procedure for the splitting tensile strength development of GPC incorporating SCMs provided the chemical compositions of each and blended material are established.